APPLICATION AND CONSTRAINTS OF BRAIN-BASED LEARNING IN PHYSICS EDUCATION - Nwoye, Amarachukwu Nkechi; Ibeanu, Juliet Ogoma; Temitayo, Shittu Ganiu (Journal of Education and Practice, 2022)
Purpose: This paper examines the application of brain-based learning in the teaching of Physics in the selected colleges of education in Oyo State. This study also seeks to identify the constraints and measure the perceptions of both students and teachers in the utilization of brain-based learning models in the teaching of Physics in the selected colleges of education. Methodology: This study adopted a quantitative research methodology in accomplishing the purpose and objectives identified. Multistage sampling was used in selecting a sample of 162 respondents (42 lecturers and 120 students). Instruments for data collection were Lecturers and Students Questionnaire Descriptive statistics (frequency and percentage counts) were used in analyzing the data. Findings: The results revealed that lecturers adopt the use of brain-based techniques in the teaching of optics, mechanics, and thermodynamics. However, in the teaching of concepts like nuclear physics relativity, and quantum mechanics the adoption level was low. A majority of lecturers further stated that this technique is only effective in a small class size. The responses of the students also point to the fact that a larger majority of them prefer a brain-based learning environment to the current teacher-focused mode of learning. Unique contribution to theory, practice and policy: It is recommended that educational training in Nigeria should focus not only on curriculum and students' management but also on models such as brain-based learning in its practical dimension.